Chlorococcales (algee: chlorophyceae) found in aquatic environments of the colombian amazon basin (1998)
Ten taxa of algae belonging to the order Chlorococcales are recorded for the first time from the Colombian Amazon basin. Two of these, Nephrocytium limneticum and Sorastrum americanum var. americanum, are recorded for the first time in Colombia.